Empirical Analysis for the Relationship between Total Productive Maintenance (TPM) Practices and Organization Performance in Energy Industry - Samsudin, Salmi; Hasnan, Norlena; Logamurthi (2019)
The importance of the energy industry motivated this research to be conducted, specifically to explore the Total Productive Maintenance (TPM) implementation in the power generation industry. TPM, as a part of management tools, has the proven capacity to improve the business performance of production in organizations. TNB Janamanjung Sdn Bhd (TNBJ) owned by Tenaga Nasional Berhad (TNB) has progressively implemented TPM since 2010. Therefore, there is a need for a research to be conducted to determine the relationship between TPM practices and the organization’s performance. Organization performance, in this research context, refers to the performance in TPM, namely equipment effectiveness, efficiency and reliability. These three measures are considered highly significant to the key performance indicators. Hence, the primary aim of this research is to investigate the relationship between TPM practices and organization performance. TPM encompasses the maintenance practice, continuous improvement, resource management and training; meanwhile, organization performance includes equipment effectiveness, autonomous maintenance and planned maintenance. The research applied the quantitative approach where the survey which was conducted received a 76 percent response rate. The results showed a significant relationship between TPM practices and organization performance. In sum, the findings support the TPM pillars model which can be the basis for TPM implementation in other industries. Besides, the findings also provide opportunities for future research to venture into different TPM practices and the effects to the organization performance